2017
DOI: 10.1074/jbc.m116.744235
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Ca2+ Depletion Differentially Modulate the Sterol Regulatory Protein PCSK9 to Control Lipid Metabolism

Abstract: Edited by Roger J. ColbranAccumulating evidence implicates endoplasmic reticulum (ER) stress as a mediator of impaired lipid metabolism, thereby contributing to fatty liver disease and atherosclerosis. Previous studies demonstrated that ER stress can activate the sterol regulatory element-binding protein-2 (SREBP2), an ER-localized transcription factor that directly up-regulates sterol regulatory genes, including PCSK9. Given that PCSK9 contributes to atherosclerosis by targeting low density lipoprotein (LDL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 85 publications
(33 reference statements)
8
38
0
Order By: Relevance
“…This form of PCSK9 SV fails to undergo autocatalytic cleavage and secretion as demonstrated previously (22). Our data demonstrate that sterol deprivation, which induces PCSK9 expression (13), was necessary to attain the SSO-induced formation of ER-resident PCSK9 SV (Fig. 3A).…”
Section: Er Retention Of a Pcsk9 Splice Variant Via Rnai Does Not Causupporting
confidence: 85%
See 2 more Smart Citations
“…This form of PCSK9 SV fails to undergo autocatalytic cleavage and secretion as demonstrated previously (22). Our data demonstrate that sterol deprivation, which induces PCSK9 expression (13), was necessary to attain the SSO-induced formation of ER-resident PCSK9 SV (Fig. 3A).…”
Section: Er Retention Of a Pcsk9 Splice Variant Via Rnai Does Not Causupporting
confidence: 85%
“…There is now ample evidence supporting the notion that the retention of PCSK9 in the ER leads to a significant reduction of circulating LDL levels. In addition, we have recently demonstrated that ER stress blocks the secretion of PCSK9 in cultured hepatocytes and mice, and this was associated with increased hepatic LDLR expression and reduced circulating LDL levels (13). Furthermore, the retention of PCSK9 in the ER via GRP94 promotes elevated hepatic LDLR levels (14).…”
Section: The Proprotein Convertase Subtilisin/kexin Type-9 (Pcsk9) Plmentioning
confidence: 99%
See 1 more Smart Citation
“…PCSK9 can contribute to atherosclerosis by targeting LDL receptor degradation. However, tunicamycin blocks PCSK9 secretion and reduces the LDL cholesterol content in plasma (Lebeau et al, 2017). Altogether, these findings suggest that ERS may interfere with lipid metabolism and that blockade of ERS may ameliorate disturbances in lipid metabolism (Figure 1).…”
Section: Ers In Lipid Metabolismmentioning
confidence: 86%
“…THP-1 or Apoe 2/2 mouse peritoneal macrophages were treated in the absence or presence of either 1 or 10 mM 4-PBA for 24 h followed by immunofluorescence microscopy as previously described by Lebeau et al (27). Briefly, cells were fixed with 4% paraformaldehyde and blocked with 1% bovine serum albumin for 30 min.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%